Microbial Food Safety Risk to Humans Associated with Poultry Feed: The Role of Irradiation. (22nd January 2019) - Mahami, Tahiru; Togby-Tetteh, Wellington; Kottoh, Delali Isaac; Amoakoah-Twum, Leticia; Gasu, Emmanuel; Annan, Sylvester Nana Yao; Larbi, Daniel; Adjei, Isaac; Adu-Gyamfi, Abraham
Abstract : Animal feed has been linked to human illness through the food chain as a result of food borne bacteria and more recently the risk of foodborne antibiotic resistance. This study investigated the extent to which radiation can be used as an intervention to improve the safety and quality of poultry feed in terms of food borne pathogens and antibiotic resistant microbes. Mean counts of control feed samples were Log10 5.98 for total viable count (TVC), Log10 4.76 for coliform count (CC), Log10 2.89 for Staphylococcus aureus count (STC), and Log10 4.57 for yeast and mold count (YMC) and Salmonella spp. (SC) was not detected (ND). All counts were within permissible levels except for CC (Log10 4.76) which was above the permissible limit of ≤ log10 4.0. Identified bacteria isolates were Enterobacter cloacae (54.5%), Bacillus cereus (27.3%), and Klebsiella pneumoniae (18.2%). All (100%) isolates exhibited multidrug Resistance (MDR) with Bacillus cereus being the most resistant (to 9 out of 11 antibiotics) followed by Enterobacter cloacae/Klebsiella pneumoniae (4 out of 11 antibiotics). Several resistance patterns were observed with PEN/AMP/FLX being the commonest (100%), followed by ERY (90.9%), TET (72.7%), CRX (66.6%), CTX (45.4%), CHL/CTR (36.4%), GEN (27.3%), and COT (18.2%). Klebsiella pneumoniae showed zero resistance to GEN/CHL/CTR/CTX/CRX while Enterobacter cloacae and Bacillus cereus exhibited zero resistance to GEN and COT, respectively. The most effective antibiotic against Gram negative bacteria ( Enterobacter cloacae and Klebsiella pneumoniae) was gentamicin while cotrimoxazole was the most effective against Bacillus cereus (Gram positive). Radiation processing of 5kGy totally eliminated all microbes including MDR food borne pathogens. In view of this, we recommend low dose radiation decontamination as a measure to mitigate against the possible food safety and public health risks to humans associated with poultry feed.